Safety, Tolerability, and Pharmacokinetics of a Long-Acting Broadly Neutralizing Human Immunodeficiency Virus Type 1 (HIV-1) Monoclonal Antibody VRC01LS in HIV-1–Exposed Newborn Infants. (2nd May 2021) - McFarland, Elizabeth J; Cunningham, Coleen K; Muresan, Petronella; Capparelli, Edmund V; Perlowski, Charlotte; Morgan, Patricia; Smith, Betsy; Hazra, Rohan; Purdue, Lynette; Harding, Paul A; Theron, Gerhard; Mujuru, Hilda; et al.
Abstract: Background: Perinatal human immunodeficiency virus type 1 (HIV-1) continues to occur due to barriers to effective antiretroviral prevention that might be mitigated by long-acting broadly neutralizing monoclonal antibodies (bNAbs). Methods: An extended half-life bNAb, VRC01LS, was administered subcutaneously at 80 mg/dose after birth to HIV-1–exposed, nonbreastfed (cohort 1, n = 10) and breastfed (cohort 2, n = 11) infants. Cohort 2 received a second dose (100 mg) at 12 weeks. All received antiretroviral prophylaxis. VRC01LS levels were compared to VRC01 levels determined in a prior cohort. Results: Local reactions (all grade ≤2) occurred in 67% and 20% after dose 1 and dose 2, respectively. The weight-banded dose (mean 28.8 mg/kg) of VRC01LS administered subcutaneously achieved a mean (standard deviation) plasma level of 222.3 (71.6) µg/mL by 24 hours and 44.0 (11.6) µg/mL at week 12, prior to dose 2. The preestablished target of ≥50 µg/mL was attained in 95% and 32% at weeks 8 and 12, respectively. The terminal half-life was 37–41 days. VRC01LS level after 1 dose was significantly greater ( P <.002) than after a VRC01 dose (20 mg/kg). No infants acquired HIV-1. Conclusions: VRC01LS was well tolerated with pharmacokinetics that support further studies of more potent long-acting bNAbs as adjunct treatment with antiretrovirals to prevent infant HIV-1 transmission. Abstract : Extended half-life broadly neutralizing antibody (bNAb), VRC01LS, administered to HIV-1–exposed infants has favorable pharmacokinetic parameters. These results support further evaluation of broad and potent bNAbs for prevention of HIV-1 transmission in infants as an adjunct to antiretrovirals.